Adolescent Girls’ Narratives on Hesitation, Realization, and Adaptation of Menstrual Hygiene and Sanitation Practices - Karki, Basanti; Subedi, Dhanapati; Dahal, Niroj (JMC Research Journal, 2024)
This paper explores the menstrual hygiene and sanitation practices of four adolescent girls from Nepali public schools. We used Bandura’s social learning theory to explain how adolescent girls learn about menstruation in a social environment. Subscribing narrative inquiry as a research methodology, we followed the first author’s journey from gathering the girls’ stories to interpreting them. Guided by the paradigm of interpretivism for understanding how they construct meaning about menstruation and menstrual hygiene amidst the diverse social scenario. We created the themes based on the girls’ (i) learning about menstruation and experiencing menarche, and (ii) practicing menstrual hygiene at home, school, and community, based on our involvement in the process of transcribing and translating the collected information, first by coding, categorizing, thematizing and theorizing. While going through the participants’ stories, we learned that the girls’ experiences are deeply rooted in their community’s social and cultural assumptions, behaviors, and practices on menstruation. They see their family, friends, and neighbors talking about menstruation, which aligns with society’s beliefs. They become accustomed to the infrastructural limitations at school and the financial constraints at home, which prevent them from comfortably practicing menstrual hygiene. As a result of the observation, the girls imitate the behaviors of other members of their family, community, and school. The findings of this study show that girls should learn about menstruation and menstrual practices from their social environment. Finally, the study suggests that home, school, and community practices be implemented to encourage girls to engage in healthier menstrual hygiene and menstruation practices.